BLOOD DESCRIPTION OF PATIN FISH (Pangasius hypopthalmus) MAINTAINED BY PHOTOPERIOD MANIPULATION AND TURMERIC-ENRICHED FEEDING - Riska Puspita Sari; Windarti Windarti; Morina Riauwaty (Berkala Perikanan Terubuk, 2020)
Physiological condition of fish is affected by environmental condition and nutrient input. The growth of Pangasius hypopthalmus is improved by reared it in short photoperiod. To understand the blood condition of P. hypopthalmus reared in manipulated and fed with turmeric enriched pellets has been conducted in July-October 2019. The fish was reared in tarp ponds, 30 fishes/pond (6-8 cm TL). Manipulated photoperiod treatments were 24 hours dark, 18 hours dark and natural photoperiod, while turmeric treatments were 0.5, 0.7, and 0.9 g/Kg feed. Parameters measured were erythrocyte total, leucocyte total, hematocrit and leucocryt of P. hypopthalmus. Result shown that in general the blood condition of the fish there were no abnormality. Blood condition of all fish treated were erythrocyte total were 2.41-2.87 x106 cells/mm3, leucocyte was 2.96-8.82 x104 cells/mm3, hematocrit were 22.9-36.2 % and leucocryt were 0.8-1.8 %. Based on data obtained it can be concluded that manipulated photoperiod and turmeric enriched pellet do not negatively impact the health status of fish in general.